(3eHGOFg ,GfhGYgs - (3YR GdOjf(B, (3adGMs ((3YeGf(B:s (3OGQ GSGeI ddfTQ h GdJhRjY(B,s, 2008)
(3jYQV gPG GdcJGH eMJhjGJg ceG jdj GdebOeI(B-(3GdaUd GdChd(B: (3eG gh GdJCejf?(B-(3GdJCejf aj GddZI(B-(3JGQjN GdJCejf(B-(3CUhd GdJCejf(B-(3JYQja GdJCejf(B-(3GdaUd GdKGfj(B: (3ehba GdTQjYI ef GdJCejf(B-(3BQGA GdabgGA aj GdJCejf(B-(3UjZI GdJCejf GdeaJi HLhGRgG(B-(3UjZI GdJCejf GdJYGhfj(B-(3GdaUd GdKGdK(B: (3GdJCejf GdJcGadj(B-(3YbO GdJCejf GdJcGadj(B-(3TQYjI GdJCejf GdJcGadj(B-(3GdaUd GdQGHY(B: (3YbO GdJCejf(B-(3bSW GdJCejf(B-(3eHdZ GdJCejf(B-(3TQcI GdJCejf GdJLGQjI(B-(3TQcI GdJCejf GddGQHMj(B-(3GdaUd GdNGeS(B: (3CfhGY hELQGAGJ GdJCejf(B-(3eHdZ GdJCejf(B-(3GdaUd GdSGOS(B: (3GdJCejf GdeKGdj deJWdHGJ Ohd GdGJMGO GdChQhHj(B-(3GdTQhW hGdHfhO(B-(3GdGSJdGe hGdJSdje(B-(3GdaUd GdSGHY(B: (3TQcGJ GdJCejf hCfhGY GdJCejf GdJj JeGQSgG(B-(3cjajI SOGO GdCbSGW(B-(3TQcI GdhWfjI ddJCejf(B-(3GdTQcI GdCgdjI ddJCejf(B-(3GdaUd GdKGef(B: (3Gdgjcd GdJfXjej dShb GdJCejf aj GdCQOf(B-(3GdaUd GdJGSY(B: (3GdEWGQ GdbGfhfj GdefXe dCYeGd GdJCejf aj GdCQOf(B-(3GdaUd GdYGTQ(B: (3HYV abQGJ GdbhGfjf GdYQHjI GdJj JJYdb HGdJCejf(B-(3GdELQGAGJ GddGReI ddMUhd Ydi NOeI bjO HSLd hSWGA GdJCejf Ch EYGOI GdJCejf(B-(3GdJCejf aj fWGb GdbGfhf(B-(3GdaUd GdMGOj YTQ(B: (3JCejf GdMhGOK GdeOQSjI(B-(3GJaGbjI GdVeGf GdeOQSj hGdQjGVj(B-(3GdaUd GdKGfj YTQ(B: (3JCejf UMj Ydi GdCWHGA hGdafjjf (B((3JCejf VO GdCNWGA GdEOGQjI(B)-(3Mbhb eYfhjI heGOjI(B-(3GdJCejf Ydi GdCYVGA GdHTQjI(B-(3GdaUd GdKGdK YTQ(B: (3JCejf CYeGd GdUGOQGJ(B-(3GdaJQI GdRefjI dGSJdGe GdHGFY fbhOg(B-(3WQjbI eWGdHI GdJCejf(B-(3GdaUd GdQGHY YTQ(B: (3CShGb GdJCejf GdYQHjI hJMQjQ GdJLGQI aj GdNOeGJ(B-(3fXQI fMh eRjO ef GdJMQjQ GdGbJUGOj(B-(3fXGe GdJCejf PO GdHWGdI(B-(3GdaUd GdNGeS YTQ(B: (3JCejfGJ GdeDSSGJ GdeUQajI(B-(3CNWGQ GdJTZjd HGdHfhc(B-(3GdaUd GdSGOS YTQ(B: (3CNWGQ JcfhdhLjG GdeYdheGJ hGdJLGQI GdEdcJQhfjI hGdMdhd GdJCejfjI GdeJGMI dJZWjJgG(B-(3JZWjI GdJCejf GdJbdjOj dJcfhdhLjG GdeYdheGJ(B-(3GdaUd GdSGHY YTQ(B: (3BQGA GdeYGQVjf dTQcGJ GdJCejf(B-(3BKGQ GdJCejf Ydi MjGI GdfGS(B-(3GdBKGQ GdEjLGHjI aj GdJCejf(B-(3BKGQ GdJCejf GdSdHjIs
(3HjHdjhZQGajG U(B.263s
Keywords: (3GdGONGQs; (3JCejfs; (3TQcGJ GdJCejfs